1976
DOI: 10.1115/1.3438996
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Optimal Design of Suspension Systems for Rotating Shafts

Abstract: A new technique is proposed for the optimum design of suspension systems for rotating shafts. In this approach the conventional method of trial and error search for optimum parameter values for a prescribed design configuration has been replaced by an efficient two-stage procedure. In the first stage a generic force is substituted for the suspension system to be designed and the absolute optimum (or limiting) performance characteristics of the shaft are computed. In the second stage, using a chosen suspension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Also, Lund and Sternlicht [5], Dworski [6], and Gunter [7] demonstrated that a signi"cant reduction in the transmitted force could be achieved by the proper design of a bearing support system. Pilkey et al [8] presented an e$cient two-stage procedure for optimizing suspension systems of rotors. From these studies, the dynamic performance problems in association with the foundation Other features such as coupling between two shafts in series, vibration isolator, vibration absorber and control actuators for vibration suppression may eventually be superimposed onto the overall system model.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Lund and Sternlicht [5], Dworski [6], and Gunter [7] demonstrated that a signi"cant reduction in the transmitted force could be achieved by the proper design of a bearing support system. Pilkey et al [8] presented an e$cient two-stage procedure for optimizing suspension systems of rotors. From these studies, the dynamic performance problems in association with the foundation Other features such as coupling between two shafts in series, vibration isolator, vibration absorber and control actuators for vibration suppression may eventually be superimposed onto the overall system model.…”
Section: Introductionmentioning
confidence: 99%
“…The objective function is optimized for each step wise increment of the speed of rotation, to predict values for support parameters for that speed. 5. IMPORTANCE OF SLOPE CONTROL 5.1.…”
Section: Scheme IImentioning
confidence: 99%
“…Researchers also reported suitable values of the support parameters that offer low UBR and high SLS. A notable work by Pilkey et al [5] applied the Linear Programming Technique to minimize the UBR. No attention was, however, paid to ®nding the SLS.…”
Section: Introductionmentioning
confidence: 99%
“…External damping at the supports is found to be useful in controlling dynamic response of rotating systems [1,2,3]. The damping in these studies has been taken to be viscous.…”
Section: Introductionmentioning
confidence: 98%